2018
DOI: 10.1002/hbm.24026
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in neural phase synchrony is related to identification of inattentional deafness in real‐world setting

Abstract: Individuals often have reduced ability to hear alarms in real world situations (e.g., anesthesia monitoring, flying airplanes) when attention is focused on another task, sometimes with devastating consequences. This phenomenon is called inattentional deafness and usually occurs under critical high workload conditions. It is difficult to simulate the critical nature of these tasks in the laboratory. In this study, dry electroencephalography is used to investigate inattentional deafness in real flight while pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 81 publications
(125 reference statements)
8
49
0
Order By: Relevance
“…In our study, the evidence of the involvement of the SMFC/pre‐SMA and the IFG in the phenomenon of inattentional deafness in ecological conditions paves the way to the use of these regions as neural signatures of this phenomenon in real‐world conditions. Taking this knowledge into account in the design of Brain Computer Interfaces monitoring alarm perception [Callan et al, ], one could develop neuroadaptive automation that could attempt to reduce the workload or to present the alarms in a more salient way when the regions associated with the attentional bottleneck are active [Régis et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the evidence of the involvement of the SMFC/pre‐SMA and the IFG in the phenomenon of inattentional deafness in ecological conditions paves the way to the use of these regions as neural signatures of this phenomenon in real‐world conditions. Taking this knowledge into account in the design of Brain Computer Interfaces monitoring alarm perception [Callan et al, ], one could develop neuroadaptive automation that could attempt to reduce the workload or to present the alarms in a more salient way when the regions associated with the attentional bottleneck are active [Régis et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the aeronautical context [Dehais et al ] confirmed that such a phenomenon could take place in the cockpit as pilots mainly rely on visual information to operate the aircraft. For instance, experiments involving high mental demand in flight simulators [Scannella et al, ] and in actual flight conditions [Callan et al, ] led to high rates of inattentional deafness with both studies showing, respectively, 56% and 55.85% missed auditory alarms.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, attentional states, such as inattentional deafness and blindness, result from the activation of an attentional network involving the inferior frontal gyrus, the insula and the superior medial frontal cortex (Tombu et al, 2011;Callan et al, 2018;Dehais et al, 2019). These regions represent potential candidates upon which to identify attentional failures that can be complemented by monitoring dedicated primary perceptual (see Hutchinson, 2019, for a review) and integrative cortices (Molloy et al, 2015), as well as performing connectivity analyses (Callan et al, 2018). In addition, inattentional phenomena may result from the suppression of activity in the right temporo-parietal junction (TPJ), a part of the ventral network, which also blocks reorientation of attention and the processing of unexpected stimuli (Marois et al, 2004;Todd et al, 2005).…”
Section: Monitoring Performance Through Degraded Mental Statesmentioning
confidence: 99%
“…MPFC (Harrivel et al, 2013;Durantin et al, 2015) DLPFC (Harrivel et al, 2013) DLPFC (Durantin et al, 2014;Fairclough et al, 2019) Left PFC (Kalia et al, 2018) occipital lobe (Kojima and Suzuki, 2010) EEG α power over occipital sites (Gouraud et al, 2018) (α and (β power (auditory stimuli) (Braboszcz and Delorme, 2011) (θ power (auditory stimuli) (Braboszcz and Delorme, 2011) N1 (Kam et al, 2011) N4 (O'Connell et al, 2009) P1 (Kam et al, 2011) P2 (Braboszcz and Delorme, 2011) P3 (Schooler et al, 2011) frontal θ power (Gärtner et al, 2014) P3 (Dierolf et al, 2017) frontal (θ power and parietal (α power (Ewing et al, 2016;Fairclough and Ewing, 2017) Event Related Coherence between midfrontal and right-frontal electrodes (Carrillo-De-La-Pena and García-Larrea, 2007) (α band power (Mathewson et al, 2009) P1 (Pourtois et al, 2006;Mathewson et al, 2009) P2 (Mathewson et al, 2009) N170 (Pourtois et al, 2006) P3 (Pourtois et al, 2006;Mathewson et al, 2009) N1 (Callan et al, 2018;Dehais et al, 2019a,b) P3 (Puschmann et al, 2013;Scannella et al, 2013;Giraudet et al, 2015b;Dehais et al, 2019a,b) (α power in IFG (Dehais et al, 2...…”
Section: Adaptation Of the User Interfacementioning
confidence: 99%
“…The N100 ERP is a neurological marker for auditory processing (Callan, et al, 2018;Hall, 1992). The N100 is a negative deflection that typically occurs between 80-150 milliseconds following the onset of an unexpected auditory stimulus (Sur & Sinha, 2009).…”
Section: N100 Componentmentioning
confidence: 99%